POLITIK PENDIDIKAN ISLAM DALAM KONFIGURASI SISTEM PENDIDIKAN DI INDONESIA - Hamlan andi (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. Islamic education in Indonesia has undergone changes and developments in the political map of national education. Changes and the development of Islamic education is influenced by the interests of political ideology and other interests in state policy-making. This is reflected by the establishment of various national education policy of the state of the position of Islamic education in the national education system since the time of Sukarno until the reign of Reform Order.Kata kunci: pendidikan Islam, politik, orde Baru, orde Reformasi